KERAJINAN LOGAM DI BANJAR PANDE KECAMATAN KEDIRI KABUPATEN TABANAN: Kerajinan logam besi - Palwika, I Ketut Andi Palwika; Rediasa, I Nyoman Rediasa; Agus, Agus Sudarmawan (Universitas Pendidikan Ganesha, 2024)
Abstract The background of this research is to determine the type and aesthetic values of Iron Metal Crafts in Banjar Pande, Kediri District, Tabanan Regency. Data was obtained through the observation and interview stages of craftsmen by analyzing domains and analyzing taxonomies. This research is a qualitative descriptive study. The aim is to find out: the types and aesthetic value of Iron Metal Crafts in Banjar Pande, Kediri District, Tabanan Regency. Thus, the results of this research are as follows: Iron Metal Crafts in Banjar Pande, Kediri District, have several models inspired by animal shapes, fictional characters and heroes which are made in a distorted manner without reducing the identity or characteristics of the object or subject being imitated.